Biological significance of GATA3, cytokeratin 20, cytokeratin 5/6 and p53 expression in muscle-invasive bladder cancer - Wang, Chung-Chieh (PLoS One, 2019)
Genetic profiling studies on muscle-invasive bladder cancers (MIBCs) have discovered molecular subtypes with different biological characteristics. Immunohistochemical (IHC) markers such as GATA3, cytokeratin (CK) 20, CK5/6, and p53 are associated with these subtypes. In this study, we investigated the biological and prognostic significance of these IHC markers in MIBCs from 91 patients who underwent radical cystectomy. High Ki-67 indices were associated with negative CK20 (p = 0.002) and diffuse CK5/6 (p = 0.001) staining. By contrast, tumors with diffuse GATA3 expression had low Ki-67 index (p = 0.006). Regarding p53, three staining patterns were associated with a high Ki-67 index: (1) complete absence, (2) diffusely strong nuclear reactivity, and (3) diffusely strong cytoplasmic staining (p < 0.001 compared with other patterns). CK5/6 and CK20 expression was typically present in a reciprocal fashion; however, diffuse GATA3 and CK5/6 coexpression was observed in 13 (14.29%) cases. Among 78 chemotherapy-naïve patients, low GATA3 staining was associated with worse recurrence-free survival in both univariate (p = 0.008) and multivariate analyses (p = 0.002). CK20, CK5/6, or p53 expression was not associated with clinical outcome. Based on our results, IHC staining for GATA3 may help risk stratification in patients with MIBC receiving radical cystectomy. In addition, the differences in Ki-67 indices suggested that aberrant p53 expression was better defined by the three aforementioned patterns, rather than percentage of nuclear staining alone.